2014
DOI: 10.1007/s00276-014-1325-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the zygomatic bone by cone beam computed tomography

Abstract: It was found an altered pattern similar to pneumatization in ZB; however, its prevalence was low (3.3% of the studied population). Our results indicate that the ZB should be evaluated in tomographic images prior to surgical treatments carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
3
15
1
Order By: Relevance
“…[20,21,25,26] however only one study by Ribeiro-Nascimento et al (2015) using CBCT has reported lower prevalence rate of 3.3%. [3] Prevalence rate as high as 68.5% also have been reported in studies conducted using CBCT. [26] Gender variation in the occurrence of ZACD Most of the studies have reported of a higher rate of occurrence in the female study subjects when compared to male study, however the difference have not been statistically significant in many of these studies.…”
Section: Prevalence Of Zygomatic Air Cell Defectmentioning
confidence: 91%
See 3 more Smart Citations
“…[20,21,25,26] however only one study by Ribeiro-Nascimento et al (2015) using CBCT has reported lower prevalence rate of 3.3%. [3] Prevalence rate as high as 68.5% also have been reported in studies conducted using CBCT. [26] Gender variation in the occurrence of ZACD Most of the studies have reported of a higher rate of occurrence in the female study subjects when compared to male study, however the difference have not been statistically significant in many of these studies.…”
Section: Prevalence Of Zygomatic Air Cell Defectmentioning
confidence: 91%
“…Although studies on ZACD have been conducted at many countries most of the published literature originates from population based studies from Iran [4,12,24,25], Turkey [16,17,18,19,20 ] India [22,23,27], USA [5,13,14], Brazil [3,21], Germany [15]. the prevalence rates of ZACD was observed to more in studies conducted on the Iranian, Turkish and American population when compared to Indian population, however it is to be noted that most of the recent studies on the later population has been conducted with CBCT therefore more prevalence was observed owing to better visualization of the ZACD.…”
Section: Ethnicity and Occurrence Of Zacdmentioning
confidence: 99%
See 2 more Smart Citations
“…These pneumatic regions can emerge at different sites including the temporal bone. The best known of these are the mastoid air cells in the temporal bone (1,2) .…”
Section: Introductionmentioning
confidence: 99%